The “Twist-Needle” – a new concept for endoscopic ultrasound-guided fine needle-biopsy - Hann, Alexander; Walter, Benjamin M.; Epp, Sonja; Ayoub, Younan Kabara; Meining, Alexander (Endoscopy International Open, 2019)
Background and study aims Endoscopic ultrasound-guided fine-needle biopsy (EUS-FNB) represents a standard method for tissue acquisition of lesions adjacent to the gastrointestinal wall. Needles of 19 gauge acquire more tissue than needles with a smaller diameter, but are often unable to penetrate solid, rigid masses. In this study we evaluated a novel prototype that links forward movement of the needle to rotation of the needle tip.Materials and methods Two needle-models that generate either a regular axial movement or a combination of axial movement with rotation of the needle tip were compared ex vivo for measurement of pressure needed to penetrate artificial tissue. Furthermore, a standard 19-gauge EUS-FNB needle was compared to a modified model (“Twist Needle”) in an ex vivo model to measure the amount of tissue obtained.Results Pressure measurements using the rotating needle revealed that significantly less pressure is needed for penetration compared to the regular axial movement (mean ± SEM; 3.7 ± 0.3 N vs. 5.5 ± 0.3 N). Using the modified 19-gauge “Twist Needle” did not diminish tissue acquisition measured by surface amount compared to a standard needle (37 ± 5 mm² vs. 35 ± 6 mm²).Conclusion The method of rotation of an EUS-FNB needle tip upon forward movement requires less pressure for penetration but does not diminish tissue acquisition. Hence, the concept of our “Twist Needle” may potentially reduce some of the current limitations of standard EUS-FNB.